CULTURAL TRADITIONS OF JUG SHAPES AMONG DON ALANS - Suhanov, Evgenij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2020)
Jugs are the most extensive category of earthenware from catacomb burial grounds of the Saltovo-Mayaki culture. They have the greatest variety of shapes among others types of ceramics. Thе present article is devoted to the study of the 211 jug shapes from six catacomb burial grounds of the Saltovo-Mayaki culture. The methodology is based on the historical-and-cultural approach to the study of vessel shapes, developed by A. A. Bobrinsky and supplemented by his modern followers. The aim of the study is to emphasize specific cultural traditions of pottery manufacture in different catacombs of the Saltovo-Mayki culture, as well as to consider such traditions among other populations that left burial mounds, and compare their historical and cultural interpretation. Based on the comparative analysis of traditions of jug shapes, the catacomb burial grounds studied here are divided into two groups. The core of the first group is formed by Dmitrievsky and Nizhnelubyansky burial grounds. Podgorovsky burial ground has many similarities with sites listed above. The second group consists of Starosaltovsky, Rubezhansky and Yutanovsky burial grounds. The grouping of burial grounds based on the traditions of jug shapes is fully consistent with their belonging to one of the two burial traditions of the Saltovo-Mayaki culture, which, according to G.E. Afanasyev, associated with different tribal groups of the Don Alans. Thus, different mass traditions of jug shapes, recorded in the Saltovo-Mayaki catacombs, have quite specific cultural and historical content. Such traditions indicate the skill differences among potters from different Alan tribal groups who settled in the middle – second half of the 8th century in the Middle Don basin, as well as the peculiarities of ideas about the exterior of vessels that existed in these communities.